The use of the biopore technique to improve soil quality and the growth of beach Casuarina plants on the reclaimed former tin mine land in Bangka Belitung Islands - Nugraha, Fadhlan; Akbar, Aji Ali; Jumiati, Jumiati (Journal of Degraded and Mining Lands Management, 2024)
The tin mining process removes soil layers so that the soil becomes dry and nutrient-poor. Reclamation of tin mining in Selingsing, Gantung Sub-district, Belitung Timur Regency, Bangka Belitung Islands Province has been carried out through revegetation using beach Casuarina plants, but plant growth is slow. On of the efforts that can be made to improve plant growth to restore land and forest conditions is using the biopore technique combined with organic litter and bioactivator solution. This study was therefore aimed to elucidate the effect of the biopore technique on soil quality and the growth of beach Casuarina on the reclaimed former tin mine land. Treatments tested were the use of bamboo biopores and without the use of bamboo biopores, with five replications in each treatment. The effect of variation was measured based on nitrogen, phosphorus, potassium, and lead contents in the root zone and plant growth (plant height and diameter). The results showed that compared to those without biopore treatment, the biopore treatment significantly increased nitrogen, phosphorus, and potassium contents by 0.67%, 2.12%, and 19%, respectively. The organic component of biopore treatment influenced the formation of metal bonds, as indicated by a decrease in lead content by 0.35%. The best plant height of 42 cm was observed in the treatment without biopore, and the best plant diameter of 2.9 cm was in the biopore treatment.